Training in Designing Mathematics Learning Using Local Context of Wetland Environment Based on Realistic Mathematics Education (RME) - Pasani, Chairil Faif; Hidayanto, Taufiq; Kamaliyah, Kamaliyah; Ridha, Muhammad Taqwa; Daris, Muhammad (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The problem in several schools is that students experience learning loss due to the COVID-19 pandemic, so several generations of students are slowly learning. Apart from that, the 2022 AKM results are less than optimal because not all students are familiar with contextual problems. Therefore, training in designing mathematics learning using the local context of the wetland environment based on RME needs to be implemented. This service aims to develop the ability of teachers of SDI Sabilal Muhtadin to design mathematics learning using the local context of the wetland environment based on RME to increase teachers' understanding and ability to design realistic learning. The method applied in this community service activity uses a PAR (Participatory Action Research) approach. The PAR cycle implemented is To Know, To Understand, To Plan, To Act, and To Change. The service team prepares material and delivers it via an offline workshop, while participants are also allowed to design learning with a local context and based on RME. The service results show an increase in teacher understanding regarding RME-based learning designs in the local context of the wetland environment, which is indicated by an increase in the average score from pre-test to post-test. Apart from that, most teachers have been able to develop mathematics learning plans based on RME in a local context. This is shown by the teacher's work in designing lessons sent to the service team. Thus, this service activity has successfully increased teachers' understanding and abilities in designing realistic learning.